KNOWLEDGE OF AGENTS OF COMMUNITY HEALTH FOOD AND NUTRITIONAL SURVEILLANCE SYSTEM ON STRATEGIES IN FAMILY HEALTH – MACAÉ (Fiep Bulletin - online, 2013)
In the health sector, the Food and Nutrition Surveillance System (Sisvan) constitutes an instrument for obtaining data for monitoring the nutritional status and dietary intake of people attending the basic units of the Brazilian National Health System (Sistema Único de Saúde - SUS). These data are generated by health professionals, able to produce information to know and disclose the nutritional epidemiological profile of the population served. The objective was to describe the knowledge of health professionals on Sisvan at the Strategies in Family Health. We conducted a descriptive study, the primary base, and cross section with the community health agents (CHA) of the Family Health Strategy (FHE) of Macaé, between August 2010 and March 2011. Scholarship Health PET, previously trained, followed the routine activities of the CHA, and interviewed using a questionnaire on knowledge about the abbreviation Sisvan and its importance in the health sector as well as the routine monitoring of nutritional status of children under 07 years. Forty-two CHA answered questions from interviewers, detecting that, in relation to knowledge, 16.7% knew the meaning of the acronym Sisvan and its importance for the health sector, 16.7% knew the meaning of the acronym, and 66 , 6% were unable or unwilling to respond. For your routine work, 47.6% explained it in detail, emphasizing that weighed fortnightly children
Keywords: Food and Nutrition Surveillance System; Community Health Agents; Public Health.